Redescription of the earthworm Moniligaster gravelyi Stephenson, 1915 (Clitellata, Moniligastridae) based on recent collections from Kerala state, India - Narayanan, S. Prasanth; Paliwal, R.; Ahmed, Shakoor; Thomas, A.p.; Julka, J.m. (Zootaxa, 2023)
Earthworms of the genus Moniligaster Perrier, 1872 can be distinguished from other genera of the family Moniligastridae by the presence of spermathecal atrial glands. Moniligaster gravelyi Stephenson, 1915 has so far been known only from a single specimen, and it is the only species with supposed single spermathecal atrial gland in the genus. Hence, this species has been a subject to some taxonomic confusion. Here, M. gravelyi is redescribed from new material collected and illustrated for the first time. The current study expanded its description and provided a more comprehensive taxonomic characterization of the species. Comparison of the species with closely related species are also made. Apart from this detailed information on its habitat and geographical range is also provided.